Numerical Study of Forced Convection of Nanofluid Flow Over a Backward Facing Step With a Corrugated Bottom Wall in the Presence of Different Shaped Obstacles - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2016)
In this paper, a numerical study of laminar forced convection of nanofluid flow over a backward facing step with a corrugated bottom wall in the presence of different shaped obstacles placed behind the step was performed. The bottom corrugated wall of the channel downstream of the step is isothermally heated and the other walls of the channel and obstacle surface are assumed to be adiabatic. The governing equations are solved with a finite-element method. The influences of the Reynolds number (between 10 and 200), solid volume fraction of the nanoparticle (between 0 and 0.05), and obstacle type (circular, square, and diamond shaped) on fluid flow and heat transfer are numerically investigated. It is observed that among different obstacles, the diamond shaped obstacle provides better local heat transfer enhancement characteristic in the vicinity of the step compared to the circular or square obstacle at high Reynolds number. Heat transfer enhancement of 6.66% is achieved in terms of maximum values with a diamond shaped obstacle compared to the no-obstacle case of the corrugated channel. Adding an obstacle deteriorates heat transfer in terms of average values for the backward facing step geometry with a corrugated wall. When the solid volume fraction of nanoparticle is increased, maximum and average heat transfer rate increase. Heat transfer enhancements of 7.45%, 7.42%, 6.94%, and 6.64% are obtained for the average values for circle, diamond, square, and no-obstacle cases, respectively, when solid volume fraction of 0.05 is compared to pure fluid.
Keywords: Heat-Transfer Characteristics; Mixed Convection; Natural-Convection; Rotating Cylinder; Vented Cavity; Parameters; Enclosure; Viscosity; Channel